SUSTAINING A COMMUNITY OF SCHOLARS AT A TRANSNATIONAL UNIVERSITY: A SELF-STUDY - Marie-Claude Toriida; Sharon Ronaldson; Bonita Fournier; Shannon Blanke (European Scientific Journal, ESJ, 2015)
In this article we report on a self-study at a transnational researchintensive university in Qatar. We trace the shared perceptions of four emerging scholars, from two disciplines, coming together to build a sustainable community of scholars as an interdisciplinary team. We explore our initial thoughts in developing our group and illustrate the themes of collegiality, mentorship and conflict in sustaining a successful community of scholars. We conclude with lessons learned illustrating how the concept of support played a significant factor in sustaining our community and adjusting to both a transnational education setting and expatriate life. The findings may serve useful to others working in such a setting, and most expressively, provide an opportunity to broaden the continued scholarly discourses of scholarship, community of scholars, and interdisciplinary teams within the context of transnational education.